Enhancement in Tribological and Mechanical Properties of Cemented Tungsten Carbide Substrates using CVD-diamond Coatings - K.A. Najar (Tribology in Industry, 2017)
An experimental investigation has been carried out to study the influence on the performance characteristics of a cutting tool material notably known as cemented tungsten carbide (WC-Co). A comparison has been documented between nanocrystalline diamond (NCD) and microcrystalline diamond (MCD) coatings deposited on two cemented tungsten carbide (WC-Co) substrates with the architectures of WC-Co/NCD and WC-Co/MCD, using hot filament chemical vapor deposition (HFCVD) technique. In the present work, the friction characteristics were studied using ball-on-disc type linear reciprocating micro-tribometer, under the application of 1–10 N normal loads, when sliding against smooth alumina (Al2O3) ceramic ball for the total duration of 20 min, under dry sliding condition. Nanoindentation tests were also conducted using Berkovich nanoindenter for the purpose of measurement of hardness and elastic modulus values. However, the average value of friction coefficient (COF) corresponding to MCD and NCD coatings decrease from ~0.37–0.32 and ~0.30–0.27, respectively when the load is increased from 1–10 N. However, for conventional WC-Co substrate the average COF increases from ~0.60–0.75, under the same input operating conditions. The wear tracks formed on the surfaces of NCD, MCD and WC-Co, after sliding were characterised using Raman spectroscopy and scanning electron microscopy (SEM) techniques. Therefore, the results will serve breakthrough information for the designer to design the cutting tool or mechanical component using this novel coating procedure.